Root Canal Configuration Evaluation on the Basis of Sectioning and Clearing Techniques - S. M. Farooq; Tahir Ali Khan; Owais Farooq (Journal of Gandhara Medical and Dental Sciences, 2014)
Objectives: Determination of Root canal configuration of maxillary first and second molar teeth was the aim of this study. Study design: An in vitro experimental study. Place and duration of the study: Study was conducted in Gandhara University for a period of six month. Materials and Methods: Specimens were analyzed by sectioning and clearing techniques for evaluation of the pattern and configuration of roots. Dye penetration was the criteria which were then evaluated through microscope. Results: In clearing group, type-I canals are 18% more than sectioning group. While type-II was reversely i.e. 19% more in sectioning group than clearing group. Conclusion: Difference in both the study groups could be mainly due to failure of dye to pass through sclerosed or minute diameter secondary canal in clearing group. This study verifies that method of research has great influence on the results.